Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/atmos12020286
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Museum Indoor Microclimate and Air Quality. Case Study from Romania

Abstract: Poor air quality inside museums is one of the main causes influencing the state of conservation of exhibits. Even if they are mostly placed in a controlled environment because of their construction materials, the exhibits can be very vulnerable to the influence of the internal microclimate. As a consequence, museum exhibits must be protected from potential negative effects. In order to prevent and stop the process of damage of the exhibits, monitoring the main parameters of the microclimate (especially tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 47 publications
0
48
0
Order By: Relevance
“…Microbiological contamination and its implications on cultural heritage frescoes were studied by Radu et al [34], Mohanu et al [35], Bucsa and Bucsa [36] and Ilies , et al [37]. Further, other relevant studies focus on the determination of fungal contamination and microclimatic problems in museums [13,[38][39][40][41], sport halls [42,43] or schools [44][45][46]. These studies have shown that among the most common fungi that can be identified in the old wooden churches on the Romanian territory are Aspergillus spp., Mucor spp., Arthrinium spp., Stachybotrys spp., Scopulariopsis spp., Penicillium spp., Absidia spp., Geotrichum spp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Microbiological contamination and its implications on cultural heritage frescoes were studied by Radu et al [34], Mohanu et al [35], Bucsa and Bucsa [36] and Ilies , et al [37]. Further, other relevant studies focus on the determination of fungal contamination and microclimatic problems in museums [13,[38][39][40][41], sport halls [42,43] or schools [44][45][46]. These studies have shown that among the most common fungi that can be identified in the old wooden churches on the Romanian territory are Aspergillus spp., Mucor spp., Arthrinium spp., Stachybotrys spp., Scopulariopsis spp., Penicillium spp., Absidia spp., Geotrichum spp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the evaluation of the attack and risk to which the museum heritage items are exposed to and not only, it is necessary to perform the assessment of the microbial load both on the surface of the item as well as in the air of the room where it is stored or exhibited within the museum etc. [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an inadequate indoor microclimate can affect the health of visitors, restorers and staff working in the museum [19,20]. This is extremely important considering that museums are usually crowded places that attract visitors belonging to all age categories, some of them implying a high degree of vulnerability (especially children and elderly).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations